2018
DOI: 10.1111/bioe.12542
|View full text |Cite
|
Sign up to set email alerts
|

Non‐therapeutic male genital cutting and harm: Law, policy and evidence from U.K. hospitals

Abstract: Female genital cutting (FGC) is generally understood as a gendered harm, abusive cultural practice and human rights violation. By contrast, male genital cutting (MGC) is held to be minimally invasive, an expression of religious identity and a legitimate parental choice. Yet scholars increasingly problematize this dichotomy, arguing that male and female genital cutting can occasion comparable levels of harm. In 2015 this academic critique received judicial endorsement, with Sir James Munby's acknowledgement tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Opponents claim that MC has no bene ts, only harms, and argue against scienti c ndings and evidence-based policies supporting the rights of parents to choose NMC for a newborn son as a desirable public health measure [72][73][74]81,83,100,104,105,111,112,157].They further argue that, even if there are bene ts, they only apply to males who are old enough to decide for themselves whether or not to get circumcised, or that the bene ts are insu cient to merit the procedure [72][73][74]83,[102][103][104][105]118]. A systematic review evaluating the various claims found them to be based on speculation or misinformation [106].…”
Section: Autonomy and Self-determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Opponents claim that MC has no bene ts, only harms, and argue against scienti c ndings and evidence-based policies supporting the rights of parents to choose NMC for a newborn son as a desirable public health measure [72][73][74]81,83,100,104,105,111,112,157].They further argue that, even if there are bene ts, they only apply to males who are old enough to decide for themselves whether or not to get circumcised, or that the bene ts are insu cient to merit the procedure [72][73][74]83,[102][103][104][105]118]. A systematic review evaluating the various claims found them to be based on speculation or misinformation [106].…”
Section: Autonomy and Self-determinationmentioning
confidence: 99%
“…Despite the lack of similarity, some opponents refer to MC as "male genital mutilation" [75], a term that appears self-serving. Opponents misconstrued a FGM case in the UK [100] by failing to note that items 72 and 73 of the judgement recognized substantial health bene ts of boyhood MC that differentiated it from FGM [146]. For a critical evaluation of the judgement by Sir James Munby, see McAllister [114].…”
Section: Legal Argumentsmentioning
confidence: 99%
“…7 In the United Kingdom, some 30,000 ritual circumcisions are performed every year, and Wheeler and Malone (2013) argue that only a few children were subsequently admitted to hospitals for treatment resulting from complications. Another study by Fox et al (2019) suggests that over 8-year period 1266 post-circumcision problems were reported by NHS authorities and that many of those complications were relatively minor. An American study showed that the incidence of male circumcision associated adverse events was slightly less than 0.5% (El Bcheraoui et al 2014).…”
Section: Risks Of Male Circumcisionmentioning
confidence: 99%
“…Early complications include cysts, irritation, urinary problems, buried penis, redundant foreskin, surgical site infection, penile skin bridge, possible altered sensitivity of the glans, glanular amputation, glanular necrosis, iatrogenic hypospadias, partial or complete amputation of the organ due to surgical error, haemorrhage and death. Late complications include inability to engage in sexual acts requiring foreskin motility, painful erections due to excessive skin removal, meatal stenosis, meatitis, phimosis, sepsis, and urethrocutaneous fistula (Munzer 2018;Fox et al 2019; WHO 2009, chap. 1; WHO April 2010a, b, p. 46; WebMD 2020).…”
Section: Critique Of the Practicementioning
confidence: 99%
“…In this chapter we seek to develop a model of embodied integrity that we have proposed elsewhere (Fox and Thomson 2017;Fox, Thomson and Warburton 2019) by applying it to the context of profoundly disabled children. We explore the role that embodied integrity might play in protecting such children from irreversible non-therapeutic bodily interventions.…”
Section: Introductionmentioning
confidence: 99%